化简 sinx+√3cosx
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 07:57:50
化简sinx+√3cosx化简sinx+√3cosx化简sinx+√3cosxsinx+√3cosx=2[(1/2)sinx+(√3/2)cosx]=2(sinxcosπ/3+cosxsinπ/3)=
化简 sinx+√3cosx
化简 sinx+√3cosx
化简 sinx+√3cosx
sinx+√3cosx
=2[(1/2)sinx+(√3/2)cosx]
=2(sinxcosπ/3+cosxsinπ/3)
=2sin(x+π/3).
化简(√3cosx+sinx)/(√3sinx-cosx)
化简sinx^2+√3sinx*cosx+2cosx^2
化简 sinx+√3cosx
化简cosx-√3sinx
化简:√3 sinX+cosX
化简√3cosx-sinx=
化简sinx/2-√3cosx/2
化简√3sinX +cosX,
化简sinx(sinx+根号3·cosx)
已知sinx-cosx=√3/3,求sinx+cosx
化简√2(sinx-cosx)
化简√2(sinx-cosx)
化简(sinx)^3+(cosx)^3
.化简:根号3sinX+cosX,
化简SINX-根号3COSX
化简(sinx+cosx)*(sinx+cosx)+sinx-cosx*cosx
化简(cos2x/sinx+cosx)-(cos2x/sinx-cosx)
化简:(1+sinx+cosx) / (1+sinx-cosx)